Modified comet assay with Giemsa staining: a suitable method for assessing genotoxicity in rats - Fagiani, M. A. B.; Fluminhan, A. [UNESP]; Araujo, E.; Reis, L. S. L. S. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The present study tested a comet assay that was modified for compatibility with Giemsa staining to assess the drug genotoxicity in the peripheral blood of rats. We analysed the peripheral blood of 16 female Wistar rats (N=8 rats/group) from a control group and from a group that was treated with an intraperitoneal injection of 50mg cyclophosphamide/kg. The comet assay was carried out with modifications of the blood volume and immersion time in the lysing solution and different combinations of electrophoresis conditions (running time, voltage and current), to Giemsa staining. The lysing time and electrophoresis conditions allowed for the expression of all classes of DNA damage during the electrophoresis run, and the comets were efficiently stained with Giemsa. The technique showed high reproducibility for the DNA classes. The results demonstrate that the modified comet assay with Giemsa staining can be standardized for routine laboratory procedures using a 20 mu L blood sample, 3h and 30min immersions in the lysing solution and electrophoresis runs with 23 to 25 V and 310 and 360mA of electrical current. The modified comet assay with Giemsa staining that was described in the present study was standardized to be applied in the laboratory routine.
Keywords: comet assay; azure stains; mutagenicity tests; genetics; electrophoresis